Warning signs mitigate deer–vehicle collisions in an Urban area - Rob Found; Mark S. Boyce (Wildlife Society Bulletin)
Abstract Increasing collisions with deer (Odocoileus spp.) and other large animals, and the rise in associated public safety risks and economic costs, have made mitigation strategies a priority for both transportation and wildlife managers. Deer‐crossing warning signage is one of the oldest forms of mitigating deer–vehicle collisions (DVCs), but despite their low cost and logistical simplicity, the effectiveness of standard‐sized permanent warning signage at reducing DVCs has not previously been adequately determined. We used historical DVC data, based on deer carcass retrieval, to identify and target areas and periods of high collision frequency. We installed warning signs at these high collision frequency locations and then compared DVCs to un‐signed control locations. The total number of DVCs at signed hotspots was significantly different in the year after the signs were installed, compared to the 3 prior years (F13 = 4.99, P = 0.004). Although the single year of posttreatment data means the long‐term efficacy of warning signage remains unknown, we showed that in the first year after installation, deer‐crossing signs targeting high collision locations can be effective at reducing DVCs. © 2011 The Wildlife Society.